A framework for re-planning of workplaces due to impact of infections. (2nd October 2021) - Meshram, Rika; Paul, Virendra Kumar; Sidana, Tarlochan Singh
We spend one-third of our lives at work and our working environment has a significant impact on our health. The outbreak of an infection in the workplace and remote working cannot replace the natural need for physical togetherness or human connections. This study aims to develop a framework for the re-planning of existing workplaces after the outbreak of infection. For developing the framework re-design needs were identified based on: (1) Literature reviews, online case examples; (2) real-time case examples, workplace design expert interviews; and (3) statutory norms by authorities. Conclusive findings indicate that various re-design measures, interventions need to be incorporated. However, there is a significant cost factor associated with it. This study gives insights into the stakeholder decision between integrating comprehensive re-design interventions and applying peripheral solutions to ensure the overall health of the workplace is not compromised.